2017
DOI: 10.1016/j.scitotenv.2017.01.168
|View full text |Cite
|
Sign up to set email alerts
|

Pollen concentrations and prevalence of asthma and allergic rhinitis in Italy: Evidence from the GEIRD study

Abstract: 47Background: Pollen exposure has acute adverse effects on sensitized individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…Consistent with other studies [17, 18], we found no associations between plant allergies and asthma morbidity, except that those with a plant-based allergy were more likely to receive specialist care for asthma. Pet allergies were also common: however, unlike a previous study demonstrating positive associations between pet allergies and asthma severity [19], we found no relationships between pet allergies and asthma morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with other studies [17, 18], we found no associations between plant allergies and asthma morbidity, except that those with a plant-based allergy were more likely to receive specialist care for asthma. Pet allergies were also common: however, unlike a previous study demonstrating positive associations between pet allergies and asthma severity [19], we found no relationships between pet allergies and asthma morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…None were statistically significant. The findings of the questionnaire survey are in agreement with an analysis of children within the ISAAC study by Burr et al [14], and of adults within the GERID study by Marchetti et al [15], where the prevalence of allergic rhinitis was inversely associated with pollen exposure.…”
Section: Discussionsupporting
confidence: 86%
“…The ECAP study showed grass and birch pollen as the sources of the most commonly sensitizing outdoor allergens [5]. While the duration and severity of allergy symptoms in sensitized individuals depend on the pollination intensity of the sensitizing taxon [6][7][8][9][10][11][12][13], the available literature does not unequivocally address the question of association between the degree of exposure to pollen in different geographical regions and the rate of sensitization among the respective populations [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Climate is associated with air pollution levels and may also act on the allergens by altering local and regional allergen production or by increasing the allergenicity of pollen (D'Amato et al 2016;Sénéchal et al 2015). Air pollution acts directly on pollen (D'Amato et al 2007), and particles carrying pollen allergen molecules are likely to play a role in the association between air pollution and respiratory allergic diseases (Bono et al 2016;Marchetti et al 2017). Finally, the level of pollen exposure is associated to allergic rhinitis incidence and prevalence and has also been associated to severity of rhinitis (Annesi-Maesano et al 2012).…”
Section: Discussionmentioning
confidence: 99%